Pengaruh Non Performing Loan (NPL) dan Capital Adequacy Ratio (CAR) terhadap Profitabilitas (Studi Kasus pada Perusahaan Perbankan yang Terdaftar di BEI Periode 2010-2013) - Putrianingsih, Dwi Indah; Yulianto, Arief (Management Analysis Journal, 2016)
The purpose of this study was to know  the influence level of Non Performing Loan (NPL) and Capital Adequacy Ratio (CAR) towards the profitability (ROA) in banking companies listed in BEI. The population in this research is the entire banking company registered in BEI in 2010-2013. Research of sampling is performed using the method of purposive sampling. Analysis  technique  used  are  multi  liniear  regression  of  ordinary  least square  and  hypotheses  test  used  is  t-statistic.  Based on the results of  the survey, encountered  that Non Performing Loan (NPL) influenced negative toward  profitability. Capital Adequacy Ratio (CAR) influential effect negatively to profitability. Suggestions from this study is banking in Indonesia should maintain the continued level of capital has improved even more capital because it can increase the profit of capital adequacy that is ROA. And then minimize bad debts or reduce the value of  pon performing loan, because with the declining value of non performing loan will increase the profits obtained by the ROA.